2012
DOI: 10.1155/2012/684157
|View full text |Cite
|
Sign up to set email alerts
|

What They Want and What They Get: Self-Reported Motives, Perceived Competence, and Relatedness in Adolescent Leisure Activities

Abstract: This study explored the extent to which adolescents' motives for leisure activity participation are related to their perceptions of competence and relatedness in different kinds of activities and aimed to provide new insight into boys' and girls' leisure experiences and their motivational orientations for activity participation. These proposed associations were based on previous empirical work and the theoretical frameworks of motive disposition approach and were tested in a nationally representative sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 53 publications
0
22
1
Order By: Relevance
“…These identified themes are also reflected in the wider leisure literature, where there is broad consensus that fun and freedom are fundamental to the experience of leisure . Opportunities for social contact and development of competence are primary motivations for engaging in leisure …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These identified themes are also reflected in the wider leisure literature, where there is broad consensus that fun and freedom are fundamental to the experience of leisure . Opportunities for social contact and development of competence are primary motivations for engaging in leisure …”
Section: Discussionmentioning
confidence: 92%
“…43,44 Opportunities for social contact and development of com-petence are primary motivations for engaging in leisure. 43,[45][46][47][48] With regard to the existing literature, the four samelevel descriptive themes resonate most strongly with SDT, and this was, therefore, used to develop the descriptive themes into analytical themes by exploring the relationships between them. SDT advances the understanding of how addressing basic psychological needs can result in the motivation to act and can foster a sense of well-being.…”
Section: Discussionmentioning
confidence: 99%
“…From the learning environment perspective, researchers (e.g., Gano-Overway, 2013;Hills, 2007;Hurtes, 2002;Leversen, Danielsen, Wold, & Samdal, 2012) have highlighted the centrality of relational development to girls' learning in physical education and identified some notable gender differences. In their examination of social interaction preferences for learning in PE among secondary students, Ruiz, Graupera, Moreno, and Rico (2010) found that girls preferred a learning environment that emphasized cooperation and affiliation, compared to the boys' preference for competition and individual achievement.…”
Section: Girls' Involvement In Physical Educationmentioning
confidence: 99%
“…According to Hills (2006Hills ( , 2007, girls give more emphasis than boys to social relationships in PE and try to include everyone. Similarly, Leversen et al (2012) reported that regardless of the physical activity, girls were more conscious of their social needs than their male counterparts.…”
Section: Girls' Involvement In Physical Educationmentioning
confidence: 99%
“…When these needs are met, motivation is self-determined and positive consequences such as less conflict ensue. The theory has been used to examine motivational influences on various behaviours including physical activity (Fortier, Williams, Sweet, & Patrick, 2009;Teixeira, Carraca, Markland, Silva, & Ryan, 2012), work (Gillet, Gagne, Sauvagere, & Fouquereau, 2012;Moran, Diefendorff, Kim, & Liu, 2012) and school (Wehmeyer, Palmer, Shogren, Williams-Diehm, & Soukup, 2013) and general leisure pursuits (Leversen, Danielson, Wold, & Samdal, 2012;Ratelle, Vallerand, Senecal & Provencher, 2005). There is a small but growing body of literature showing that self-determined motivation toward conflicting goal pursuits reduces reported conflict due to the harmonious integration of the goals into the self concept (Ratelle et al, 2005;Senecal, Vallerand, & Guay, 2001).…”
Section: Relationship Between Self-determination and Goal Conflictmentioning
confidence: 99%